2016
DOI: 10.1002/hbm.23272
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery Induces White and Grey Matter Density Recovery in the Morbidly Obese: A Voxel‐Based Morphometric Study

Abstract: Obesity is associated with lowered brain's grey (GM) and white matter (WM) density as measured by voxel-based morphometry (VBM). Nevertheless, it remains unknown whether obesity has a causal influence on cerebral atrophy. We recruited 47 morbidly obese subjects (mean BMI = 42.2, SD = 4.0, 42 females and five males) eligible for bariatric surgery and 29 non-obese subjects (mean BMI = 23.2, SD = 2.8, 23 females and six males) served as controls. Baseline scans were acquired with T1-weighted magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 44 publications
11
59
0
Order By: Relevance
“…Imaging studies in humans previously reported that obese individuals have reduced WM tissue density and altered WM integrity in dispersed tracts, including the corpus callosum, cingulum, cerebellar peduncle and corona radiata (9,12,13,17,19,29,43). These findings align well with our cross-sectional results showing that WM density in brain stem and cerebellar peduncle, two regions that significantly increased after SG, were reduced in severely obese individuals compared to normal-weight individuals.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Imaging studies in humans previously reported that obese individuals have reduced WM tissue density and altered WM integrity in dispersed tracts, including the corpus callosum, cingulum, cerebellar peduncle and corona radiata (9,12,13,17,19,29,43). These findings align well with our cross-sectional results showing that WM density in brain stem and cerebellar peduncle, two regions that significantly increased after SG, were reduced in severely obese individuals compared to normal-weight individuals.…”
Section: Discussionsupporting
confidence: 91%
“…As previously reported by other groups (9,29), we observed that bariatric surgery-induced weight loss was associated with increased global WM density, particularly in the cerebellum, brain stem, cerebellar peduncle, cingulum, corpus callosum and corona radiata.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations